Can periodontitis affect the COVID-19 severity, symptoms, hospital stay, and mortality? A case-control study - Shravya Macherla; Aditi Chopra; Venkitachalam Ramanarayanan; Rajat Subra Das; Rupesh Garg (Frontiers Media S.A., 2024)
Background/purposePoor oral hygiene and periodontal disease have been identified as potential risk factors for the coronavirus disease 2019 (COVID-19). The present study aimed to determine the association between periodontitis and COVID-19 severity, nature of symptoms, mortality, and hospital stay.MethodsIn total, 163 COVID-19-positive patients (men: 93; women: 70) were categorized into two groups: the control group, consisting of 120 patients with asymptomatic or mild symptoms, and the case group, consisting of 43 patients with moderate-to-severe symptoms. The severity of periodontal disease, oral hygiene status (OHI), pocket depth (PD), bleeding on probing (BOP), number of decayed/missing/filled teeth, mortality, duration of stay in the hospital, oxygen requirement, and nature of COVID-19 symptoms were assessed in both groups. The association between periodontitis and COVID-19 was analyzed with other confounding factors such as age, sex, comorbidities, oral hygiene, and smoking status.ResultsThe presence of periodontitis increases the severity of COVID-19 by 3.7 times (p = 0.002). A statistically significant difference was noted for symptoms such as dizziness (p = 0.036), running nose/cold (p = 0.009), and headache (p = 0.005) in the presence of periodontitis. The risk estimate for death associated with periodontitis was 1.03. Additionally, the average duration of stay was longer for individuals with periodontitis than for those in the control group.ConclusionThere is a positive association between periodontal disease and COVID-19. Periodontitis increases the severity of COVID-19 and alters the symptoms. Hence, periodontal disease management should be an integral part of managing patients with coronavirus infection.